2015
DOI: 10.1002/rnc.3319
|View full text |Cite
|
Sign up to set email alerts
|

Robust Kalman filtering for nonlinear multivariable stochastic systems in the presence of non‐Gaussian noise

Abstract: SUMMARYThe presence of outliers can considerably degrade the performance of linear recursive algorithms based on the assumptions that measurements have a Gaussian distribution. Namely, in measurements there are rare, inconsistent observations with the largest part of population of observations (outliers). Therefore, synthesis of robust algorithms is of primary interest. The Masreliez-Martin filter is used as a natural frame for realization of the state estimation algorithm of linear systems. Improvement of per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
52
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(52 citation statements)
references
References 29 publications
0
52
0
Order By: Relevance
“…These results are extended to develop a robust EKF by using a matrix forgetting factor in [21]. Simulations results in [18][19][20][21] show that robust filters outperform the standard EKF when the noise covariances used in the robust filters and the truth are mismatched. Although it is straightforward and simple to develop robust EKF, the EKF suffers from its own drawbacks such as instability due to linearization and costly calculation of Jacobian matrices.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…These results are extended to develop a robust EKF by using a matrix forgetting factor in [21]. Simulations results in [18][19][20][21] show that robust filters outperform the standard EKF when the noise covariances used in the robust filters and the truth are mismatched. Although it is straightforward and simple to develop robust EKF, the EKF suffers from its own drawbacks such as instability due to linearization and costly calculation of Jacobian matrices.…”
Section: Introductionmentioning
confidence: 90%
“…For state estimation of nonlinear stochastic systems, extensions and generalizations have been proposed such as the robust extended Kalman filter (EKF) [18][19][20][21] and the Huber-based divideddifference filter [22,23]. In [18], the Masreliez-Martin method was used to develop a robust EKF in the case when the process noise has a Gaussian distribution and the measurement noise has a nonGaussian distribution.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, the recursive estimation method was developed by employing the minimum mean square error principle and the projection theory. Accordingly, a considerable number of research results were reported to design the optimal filters in many practical systems [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%